A Scoping Review of Decolonization in Indigenous-Focused Health Education and Behavior Research. (June 2021) - Narasimhan, Subasri; Chandanabhumma, P. Paul
Public health remains acutely affected by the historical legacy and ongoing processes of colonization. Although scholars have advocated for decolonization of public health systems, the principles and processes of decolonization have not been explicitly elaborated nor applied broadly within the field. To map these concepts, we conducted a scoping review of decolonization of the Indigenous-focused health behavior and education literature. Following the JBI (formerly Joanna Briggs Institute) scoping review framework, we conducted searches in PubMed, PsycINFO, and Web of Science using key search terms: "health education, " "health behavior, " "health promotion, " "health practice" AND "decolonization" or "decolonial." We also conducted targeted searches of key journals to ensure review completeness. For selected articles, we examined the article content, focal population, country context and health condition(s). We assessed for the definition of decolonization (if provided), descriptions of decolonial processes used (if stated), and the application of the decolonial processes (e.g., for research, intervention, or critique, etc.). Characteristics of decolonial processes were grouped by those that were similarly described leading to the generation of common themes of reflection, action, and planning . Our review suggests that no clear norms exist in conceptualizing the definitions and processes of decolonization in the reviewed literature. A small proportion of the articles articulate decolonial processes in manners that are consistent, cohesive and attentive to the goals of decolonization. We believe that this review will encourage public health practitioners to consider meaningful approaches to challenging colonizing structures and engage with community partners to advance the visions of social justice and health equity.